2020
DOI: 10.1186/s41065-020-00129-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between methylenetetrahydrofolate reductase gene rs1801131 A/C polymorphism and urinary tumors’ susceptibility

Abstract: Background: The methylenetetrahydrofolate reductase (MTHFR) rs1801131 A/C variant results in a decrease in MTHFR enzymatic activity, which may play an important role in folate metabolism and is also an important source of DNA methylation and DNA synthesis. Several case-control studies have been conducted to assess the association of MTHFR rs1801131 polymorphism with the risk of urinary cancers, yet with conflicting conclusions. To derive a more precise estimation of above relationship, the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Generally, no statistically significant association was observed between the rs1801131 polymorphism and the risk of developing BC. These results are supported by the work of Shi et al and Xu et al [46], [47]. On the other hand, it is interesting to highlight that the subgroups' analysis related to geographic regions revealed a protective effect of the rs1801131 allele in the North American population.…”
Section: Rs1801131supporting
confidence: 70%
“…Generally, no statistically significant association was observed between the rs1801131 polymorphism and the risk of developing BC. These results are supported by the work of Shi et al and Xu et al [46], [47]. On the other hand, it is interesting to highlight that the subgroups' analysis related to geographic regions revealed a protective effect of the rs1801131 allele in the North American population.…”
Section: Rs1801131supporting
confidence: 70%
“…It was found that the rs1801133 (677C>T) in exon 4 and rs180113 (1298A>C) in exon 7 of the MTHFR gene resulted in amino acid substitution and a reduction of MTHFR activity ( Liu et al, 2020). To date, several epidemiological studies have evaluated the association of MTHFR rs1801133 (677C>T) and rs180113 (1298A>C) polymorphisms with susceptibility to bladder cancer (You et al, 2013;Xu and Zuo, 2020). However, these associations were still inconclusive.…”
Section: Introductionmentioning
confidence: 99%